Core‐Shell Type Semiconducting Heterostructures for Visible Light Photocatalysis. Issue 5 (16th October 2019) - Ganguli, Ashok Kumar; Das, Anirban; Natarajan, Kalithasan
Abstract: This personal account highlights a part of the work done over the years in our group towards directed synthesis of morphologically controlled nanostructures. We begin with our efforts on the synthesis of families of nanostructured metal oxides and metal oxalates of well‐defined morphology using low temperature microemulsion and hydrothermal techniques. The parameters that govern the morphology in these syntheses e. g. choice of solvent and temperature are described. We then discuss nanostructures with core‐shell architecture and specifically their utilization to harvest visible light for photocatalysis and photoelectrochemical applications. The techniques described to utilize visible light include sensitizing wide bandgap semiconductors using 1) appropriate narrow bandgap materials and 2) metals that have surface plasmon resonance active bands. The reports are classified according to morphology with spherical, cubes and rods discussed in separate sections. A discussion of recent reports by other groups on core‐shell structures of similar composition as well as future directions and perspectives are presented at the end.   Abstract : Reviews work done in our group and similar recent work from other groups on photo(electro)catalytic activity of morphologically controlled semiconductor based nanostructured systems having a core‐shell architecture.